Joseph Arthur Moore papers - Moore, Joseph Arthur, 1879-1937.
Chiefly letters, telegrams, and memoranda between Moore and William Randolph Hearst concerning newspaper operations and policy, local and national politics, and Hearst's magazine and motion picture interests. Includes correspondence with Arthur Brisbane, Robert W. Chambers, Millicent Willson Hearst, and Ray Long. Also includes articles concerning Hearst and other papers.
Publisher and newspaperman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brisbane, Arthur, -- 1864-1936 -- Correspondence; Chambers, Robert W. -- 1865-1933 -- Correspondence; Hearst, Millicent Willson -- Correspondence; Hearst, William Randolph, -- 1863-1951.; Hearst, William Randolph, -- 1863-1951 -- Correspondence; Long, Ray, -- 1878-1935 -- Correspondence; American newspapers; American periodicals; Motion pictures; United States -- Politics and government -- 1901-1953.; Newspapermen; Publishers